Mechanisms of Oxidative Damage in Multiple Sclerosis and Neurodegenerative Diseases: Therapeutic Modulation via Fumaric Acid Esters - Lee, De-Hyung (Molecular Diversity Preservation International (MDPI), 2012)
Oxidative stress plays a crucial role in many neurodegenerative conditions such as Alzheimer’s disease, amyotrophic lateral sclerosis and Parkinson’s as well as Huntington’s disease. Inflammation and oxidative stress are also thought to promote tissue damage in multiple sclerosis (MS). Recent data point at an important role of anti-oxidative pathways for tissue protection in chronic-progressive MS, particularly involving the transcription factor nuclear factor (erythroid-derived 2)-related factor 2 (Nrf2). Thus, novel therapeutics enhancing cellular resistance to free radicals could prove useful for MS treatment. Here, fumaric acid esters (FAE) are a new, orally available treatment option which had already been tested in phase II/III MS trials demonstrating beneficial effects on relapse rates and magnetic resonance imaging markers. In vitro, application of dimethylfumarate (DMF) leads to stabilization of Nrf2, activation of Nrf2-dependent transcriptional activity and abundant synthesis of detoxifying proteins. Furthermore, application of FAE involves direct modification of the inhibitor of Nrf2, Kelch-like ECH-associated protein 1. On cellular levels, the application of FAE enhances neuronal survival and protects astrocytes against oxidative stress. Increased levels of Nrf2 are detected in the central nervous system of DMF treated mice suffering from experimental autoimmune encephalomyelitis (EAE), an animal model of MS. In EAE, DMF ameliorates the disease course and improves preservation of myelin, axons and neurons. Finally, Nrf2 is also up-regulated in the spinal cord of autopsy specimens from untreated patients with MS, probably as part of a naturally occurring anti-oxidative response. In summary, oxidative stress and anti-oxidative pathways are important players in MS pathophysiology and constitute a promising target for future MS therapies like FAE.